Controlling the World Bank and IMF : shareholders, stakeholders, and the politics of concessional lending - Clegg, Liam, 1981- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2013)
Provides an innovative reading of where power lies in the institutions' concessional lending operations, drawing its focus on shareholders and stakeholders from staffs' own understandings of their operational environments.
Includes bibliographical references (pages 179-209) and index.
oif 12/06/15
Loan
Keywords: World Bank; International Monetary Fund; Financial institutions, International; Economic assistance; Economic development